Ethics and Images of Pain. - Grønstad, Asbjørn (Routledge advances in art and visual studies., 2012)
Few phenomena are as formative of our experience of the visual world as displays of suffering. But what does it mean to have an ethical experience of disturbing or traumatizing images? What kind of ethical proposition does an image of pain mobilize? How may the spectator learn from and make use of the painful image as a source of ethical reflection? Engaging with a wide range of visual media--from painting, theatre, and sculpture, to photography, film, and video--this interdisciplinary collection of essays by leading and emerging scholars of visual culture offers a reappraisal of the increasin.